PERTUMBUHAN DAN PRODUKSI BUNGA MATAHARI (Hellianthus annus.L) PADA DUA JENIS MEDIUM YANG DIBERI KOMPOS TANDAN KOSONG KELAPA SAWIT - Mia Audina; Wawan Wawan; Husna Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Research on sunflower in Riau has not ever been studied, therefore this study is planted using  planting medium that is soil dominated by Ultisol and Inceptisol. soil improvement  with using oil palm empty fruit bunches (EFB) compost can increase the growth and yield of the sunflower plant. The experiment was conducted with a split plot design (split plot) in the form of 4 x 2 factorial, the first factor is the Plant Media And the second factor is the administration of EFB compost that consists of four levels of 0g, 25g, 50g, and 75g. Data were statistically analyzed by analysis of variance and Duncan's multiple range test (DMRT) at 5%. Parameters measured were plant height, leaf number, date of flowering, harvest, seed weight, and the analysis of soil chemical properties. The results of the study found that the application of 50g / polybag EFB compost was the best treatment for the growth and yield of the sunflower on Ultisols media and Inceptisols.Keywords: Sunflower, Ultisol, Inceptisol, EFB, Split Plot